Rational Design of Nanostructured Metal/C Interface in 3D Self‐Supporting Cellulose Carbon Aerogel Facilitating High‐Performance Li‐CO2 Batteries. Issue 20 (11th April 2022) - Liu, Limin; Qin, Yanyang; Wang, Ke; Mao, Heng; Wu, Hu; Yu, Wei; Zhang, Dongyang; Zhao, Hongyang; Wang, Hairong; Wang, Jiuhong; Xiao, Chunhui; Su, Yaqiong; et al.
Abstract: The sluggish kinetics of CO2 reduction and evolution reaction (CRR and CER) on the Li–CO2 battery cathode seriously hindered its practical application. Rational design of the Ru/C interface is expected to simultaneously decrease the free energy barrier of intermediate species and create a favorable electronic structure, effectively promoting the catalytic reaction kinetics of the CRR and CER. Herein, a 3D self‐supporting cellulose carbon aerogel (CCA) with well‐defined Ru/C interfaces (Ru@CCA) is synthesized as an advanced CO2 ‐breathing cathode for Li–CO2 batteries. The results show that the energy efficiency significantly improves to 80% with a high discharge capacity of 10.71 mA h cm −2 at 20 µA cm −2, and excellent cyclic stability of 421 cycles at 100 µA cm −2 . These outstanding performances are highly competitive compared with state‐of‐art Li–CO2 cathodes. In addition, the unique interface design strategy is applied to other non‐noble metal@CCA cathodes, which confirms the advantages of constructing nanostructure metal/C interfaces for improving the kinetics of CRR and CER. This fundamental understanding of the structure–performance relationship provides new inspiration for designing highly efficient cathode catalysts for Li–CO2 batteries. Abstract : An attractive solution for developing an integrated hybrid catalyst for Li–CO2 batteries is presented by constructing metal/C active sites on 3D self‐supporting cellulose carbon aerogel (CCA). This work's fundamental understanding of the structure‐performance relationship between metal nanoparticles and CCA support provides new inspiration and guidelines to design highly efficient cathode catalysts for Li–CO2 batteries.